Answer:
f(x) = (x + 3)(x − 1)(x − 4)
Explanation:
the graph starts at the bottom left and continues up through the x axis at negative three to a maximum around y equals twenty and goes back down through the x axis at one to a minimum around y equals negative twelve point five and back up through the x axis at four
for a graph, the y axis is the vertical part of the graph, the x axis is the horizontal
following the instruction given , you notice that
x=-3
x=1
x=4
therefore
f(x) = (x + 3)(x − 1)(x − 4)
(x + 3)(x − 1)(x − 4)